Azasugar analogues: conformationally restricted vicinal diamine derived from (S)-(-)-pyroglutamic acid - Chan, P; Cottrell, I; Moloney, M (1999)
The preparation of a diamino substituted pyrrolidinone system in a diastereoselectively controlled manner is described. The procedure employed made use of electrophilic amination of a chiral bicyclic γ-lactam, which when subjected to sequential deprotection provided a simple route to a 3,4- diaminopyroglutaminol. The chemoselective deprotection of the amino functionality was also shown to be possible under mild hydrogenolytic conditions.